ANALISIS KEBUTUHAN PEMBELAJARAN DI MADRASAH IBTIDAIYAH: PENYESUAIAN KARAKTERISTIK, KURIKULUM, CAPAIAN DAN MEDIA PEMBELAJARAN SESUAI KEBUTUHAN PESERTA DIDIK - Wilda Al Aluf; Sutiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the learning needs at Madrasah Ibtidaiyah with a focus on four main aspects: student characteristics, the implemented curriculum, expected learning outcomes, and the teaching media used. We use a qualitative literature study method to analyze relevant literature, including books and journals. Theories related to this topic serve as the data sources. The research results show that the characteristics of students in Madrasah Ibtidaiyah include cognitive, emotional, social, motivational, moral, and motor aspects that interact with each other in the learning process. By understanding individual differences, teachers can manage the classroom more effectively and choose appropriate learning media to support the participation of all students. The curriculum functions as a tool for achieving educational objectives, incorporating crucial elements that facilitate its effective implementation. In Madrasah Ibtidaiyah, students aim to achieve learning achievements, which encompass aspects of knowledge, skills, and attitudes that align with the applicable curriculum. This process involves the interaction between new experiences and previous experiences, which contributes to changes in students' attitudes and behaviors. Madrasah Ibtidaiyah expects this research to provide insights for the development of more effective learning strategies. Thus, a comprehensive understanding of student characteristics and the curriculum will enhance the quality of education at the primary level.